토픽의 조합으로 이벤트 흐름을 예측하기 위한 시각적 분석 시스템 - 연한별(Hanbyul Yeon); 김석연(Seokyeon Kim); 장윤(Yun Jang) (정보과학회 컴퓨팅의 실제 논문지, 2015)
사회적 혼란을 야기하는 이벤트는 발생 직후 어떻게 대응하느냐에 따라 소요되는 비용의 편차가 크다. 이에 따라 비정상적인 이벤트를 탐지하고 의미를 파악하는 연구가 많이 진행되고 있다. 또한 예측 분석에 관한 연구도 많이 수행되고 있다. 그러나 대부분의 연구는 이벤트의 전체적인 미래 경향에 대한 수치 결과를 예측할 뿐, 이벤트가 내포하는 의미에 대한 예측 연구는 미비하다. 이에 따라 본 논문에서는 비정상적인 이벤트가 내포하는 토픽의 조합을 통해 미래에 어떠한 일이 발생할 수 있는지에 대한 시각적 예측 분석 방법을 제안한다. 제안하는 방법은 먼저 트윗에서 실시간으로 비정상 이벤트를 탐지한다. 그 다음 과거 유사한 사례를 탐색한 다음 이벤트와 관련된 토픽들을 추출한다. 마지막으로 사용자는 의미 있는 토픽의 조합을 통해 미래에 어떠한 일이 발생할 수 있을지 분석할 수 있다. 실험은 두 가지 상황에 대한 예측 분석을 수행하였으며, 실험 결과 본 논문에서 제안한 방법의 타당성을 입증하였다. Emergence events are the cause of much economic damage. In order to minimize the damage that these events cause, it must be possible to predict what will happen in the future. Accordingly, many researchers have focused on real-time monitoring, detecting events, and investigating events. In addition, there have also been many studies on predictive analysis for forecasting of future trends. However, most studies provide future tendency per event without contextual compositive analysis. In this paper, we present a predictive visual analytics system using topic composition to provide future trends per event. We first extract abnormal topics from social media data to find interesting and unexpected events. We then search for similar emergence patterns in the past. Relevant topics in the past are provided by news media data. Finally, the user combines the relevant topics and a new context is created for contextual prediction. In a case study, we demonstrate our visual analytics system with two different cases and validate our system with possible predictive story lines. KCI Citation Count: 0